Low cost multi-touch human computer interface - Rohit Jha. (2011)
Multi-touch refers to a touch system's ability to simultaneously detect and resolve a minimum of 3+ touch points. Multi-touch is one of the key techniques of implementing the concept of Human Computer Interaction. The speed, efficiency and intuitiveness of the technology have resulted in its widespread popularity, with many companies doing rapid research in this area. This technology has its applications varying from elementary education like in schools to specialized implementation like in space research centers. But the basic problem with such systems is the exponential increase in cost with the increase in complexity and size of the system.